A Case of Primary Lung Adenocarcinoma With Recurrent Brain Metastasis due to Transformation to Small Cell Carcinoma During Adjuvant Atezolizumab Therapy - Nao Kobayashi; Noriaki Sunaga; Masakiyo Yatomi; Ikuo Wakamatsu; Sohei Muto; Hayato Ikota; Rei Yamaguchi; Yoichi Ohtaki; Toshiteru Nagashima; Nobuteru Kubo; Tomomi Masuda; Yosuke Miura; et al. (Thoracic Cancer)
ABSTRACT Histologic transformation from non‐small cell to small cell lung cancer (SCLC) is a resistance mechanism to immune checkpoint inhibitors. We report herein a case of lung adenocarcinoma who developed liver and brain metastases during adjuvant atezolizumab therapy. The patient underwent a craniotomy to resect a brain metastasis, which was pathologically diagnosed as SCLC. He subsequently received platinum‐based chemotherapy with durvalumab, resulting in sustained regression of the liver metastases. This case demonstrates a metastatic brain tumor‐acquired resistance to atezolizumab through histologic transformation from adenocarcinoma to SCLC. Therefore, rebiopsy is needed if recurrent disease appears during immune checkpoint inhibitor treatment in patients with non‐small cell lung cancer.